EVALUATION OF RESPONSE TO ANTIHYPERTENSIVE’S IN PREECLAMPSIA AND GESTATIONAL HYPERTENSION CASES WITH DIFFERENT ACE GENE INSERTION/DELETION GENOTYPES - Afreen, Arshiya; Ali, Fatma; Aziz, Juhi; Makeen, Nida; Fathima, Nusrath; P, Padmaja; MOHD MOHIUDDIN; Ishaq, Mohd (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this research study was to investigate if there exists a relationship between angiotensin converting enzyme (ACE) genes insertion/deletion (I/D) genotypes and the antihypertensive treatment being received by preeclampsia (PE) and gestational hypertension (GH) patients. Methods: A total of 50 PE and 35 GH cases were included. ACE gene I/D genotyping was carried out on the blood samples of cases and correlated with the antihypertensive treatment being received by these patients. Details of antihypertensives being received by them were nifedipine (a calcium channel blocker 10 mg) and methyldopa (an alpha 2 receptor agonist 250 mg) which is considered as the first-line of treatment. 30 normotensive pregnant women of comparable gestational period served as controls. Results: It was observed that a combination of calcium channel blocker (nifedipine 10 mg), as well as alpha 2 agonist (methyldopa 250 mg), was required in patients with D' allele containing genotypes. However, PE and GH patients with II genotype as well as those of GH patients responded well to either nifedipine or methyldopa. If confirmed these results appear to be of clinical significance as prior knowledge of ACE I/D genotypes will be useful in the management of PE cases in general and severe PE cases in particular. Conclusion: Prior knowledge of ACE I/D genotypes appears to be helpful in the management of PE and GH cases.